The Usefulness of Magnetic Resonance Imaging of the Cardiovascular System in the Diagnostic Work-Up of Patients With Turner Syndrome - Obara-Moszynska, Monika; Rajewska-Tabor, Justyna; Rozmiarek, Szymon; Karmelita-Katulska, Katarzyna; Kociemba, Anna; Rabska-Pietrzak, Barbara; Janus, Magdalena; Siniawski, Andrzej; Mrozinski, Bartlomiej; Graczyk-Szuster, Agnieszka; Niedziela, Marek; Pyda, Malgorzata (Frontiers in Endocrinology, 2018)
Cardiovascular defects occur in 50% of patients with Turner syndrome (TS). The aim of the study was to estimate the usefulness of cardiac magnetic resonance imaging (CMR) and magnetic resonance angiography (angio-MR) as diagnostics in children and adolescents with TS. Forty-one females with TS, aged 13.9±2.2 years, were studied. CMR was performed in 39 patients and angio-MR in 36. Echocardiography was performed in all patients. The most frequent anomalies diagnosed on CMR and angio-MR were as follows: elongation of the ascending aorta and aortic arch, present in 16 patients (45.7%), a bicuspid aortic valve (BAV), present in 16 patients (41.0%), and partial anomalous pulmonary venous return (PAPVR), present in 6 patients (17.1%). Aortic dilatation (Z-score>2) was mostly seen at the sinotubular junction (15 patients; 42.8%), the ascending aorta (15 patients; 42.8%), the thoracoabdominal aorta at the level of a diaphragm (15 patients; 42.8%) and the transverse segment (14 patients; 40.0%). An aortic size index (ASI) above 2.0 cm/m2 was present in 6 patients (17.1%) and above 2.5 cm/m2 in 3 patients (8.6%). The left ventricular end-diastolic volume (EDV), end-systolic volume (ESV) and stroke volume (SV) were diminished (Z-score< -2) in 10 (25.6%), 9 (23.1%) and 8 patients (20.5%) respectively. A webbed neck was correlated with the presence of vascular anomalies (p=0.006). The age and body mass index (BMI) were correlated with the diameter of the aorta. Patients with BAV had a greater aortic diameter at the ascending aorta (AA) segment (p=0.026) than other patients. ASI was correlated with aortic diameter and descending aortic diameter (AD/DD) ratio (p=0.002; r=0.49). There was a significant correlation between the right ventricular (p=0.002, r=0.46) and aortic diameters at the sinotubular junction segment (p=0.0047, r=0.48), as measured by echocardiography and CMR. Magnetic resonance can identify cardiovascular anomalies, dilatation of the aorta, pericardial fluid and functional impairment of the ventricles not detected by echocardiography. BMI, age, BAV and elongation of the ascending aorta influence aortic dilatation. The ASI and AD/DD ratio are important markers of aortic dilatation. The performed diagnostics did not indicate a negative influence of GH treatment on the cardiovascular system.